Analisis Studi Kelayakan Bisnis Ekspansi Pasar Pada UMKM CV Siraj Fawwaz Di Wilayah Ciwidey Kabupaten Bandung - Andi Gunawan; Dede Ramadani; Iqbal Saepul Huda; Ranti Nursyaban; Vega Permana; Aceng Kurniawan (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Business Feasibility Study measurement needs to be done as testing material in carrying out business developments carried out. In this case, CV Siraj Fawwaz conducts business development by expanding the market as a form of business development by adjusting to market trends that develop today. This study aims to analyze the business feasibility that will be developed by CV Siraj Fawwaz. The method used in this study is to use the ratio analysis method from the data obtained through interviews with business owners CV Siraj Fawwaz. The results of this study were determined through several business feasibility study analyses with the results: 1) Ppayback Period (PP) showing results of 3 years 9 months means PP less than investment time, then CV Siraj Fawwaz's business development is declared feasible; 2) Profitability Index (PI) shows a result of 3.31 means that the PI is more than one, then the business development carried out by CV Siraj Fawwaz is declared feasible; 3) Net Present Value (NPV) shows a result of 3,680,592.58, NPV value shows a positive value meaning that the business development of CV Siraj Fawwaj is declared feasible; 4) Internal Rate Of Return (IRR) showed a result of 18.42%, meaning that IRR's position was between NPV1 and NPV2, so CV Siraj Fawwaj's business development was declared feasible; and 5) Break Event Point (BEP) in CV Siraj Fawwaj's business development will be declared breakeven if BEP per unit is 6,353 and BEP per rupiah is IDR 95,290,702 for 2023.